2021
DOI: 10.1021/acs.jmedchem.0c01487
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Bromodomain and Extraterminal Proteins for Drug Discovery: From Current Progress to Technological Development

Abstract: Bromodomain and extraterminal (BET) proteins bind acetylated lysine residues in histones and nonhistone proteins via tandem bromodomains and regulate chromatin dynamics, cellular processes, and disease procession. Thus targeting BET proteins is a promising strategy for treating various diseases, especially malignant tumors and chronic inflammation. Many pan-BET small-molecule inhibitors have been described, and some of them are in clinical evaluation. Nevertheless, the limited clinical efficacy of the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 132 publications
2
71
0
Order By: Relevance
“…These clinical trials have been reviewed by Tang et al recently. [116] BETis reprogram pathological transcriptional program, triggering either cell death or cell cycle arrest in cancer. Preclinical studies have also revealed the beneficence of using BETi to treat seizures, [66] RTT, [107] inflammatory diseases and LPS-induced sepsis, [117] as well as mitochondrial diseases with Complex I mutations.…”
Section: The Development and Application Of Bet Inhibitors (Betis)mentioning
confidence: 99%
See 1 more Smart Citation
“…These clinical trials have been reviewed by Tang et al recently. [116] BETis reprogram pathological transcriptional program, triggering either cell death or cell cycle arrest in cancer. Preclinical studies have also revealed the beneficence of using BETi to treat seizures, [66] RTT, [107] inflammatory diseases and LPS-induced sepsis, [117] as well as mitochondrial diseases with Complex I mutations.…”
Section: The Development and Application Of Bet Inhibitors (Betis)mentioning
confidence: 99%
“…Inhibition of BRD4 leads to dysfunctions of the digestive system, fragile, hyperbilirubinemia, thrombocytopenia, anemia, metabolic disorders, and hyperglycemia. [116] Some of these impacts may be due to the vulnerability of normal proliferative cells to BETis. [122] Negative effects of BETis on the nervous system and immune system have not been reported, but they should be scrutinized in clinical trials as BRD4 is also essential in these systems.…”
Section: Issues Surrounding Current Betismentioning
confidence: 99%
“…The bromodomain and extraterminal (BET) family, including BRD2, BRD3, BRD4 and BRDT, can recognize N -acetyl lysine post-translational modifications on histone tails, each of which contains two conserved bromodomains named BD1 and BD2 1 , 2 , 3 . BD1 is mainly regarded as a chromatin-binding module and BD2 is typically used for transcription factor recruitment 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…There are over 40 clinical trials of BRD4 inhibition, most of them are used for malignant tumors and leukemia 3 , 10 , 11 , 12 . However, the occurrence of side effects, modest clinical efficacy and preclinical resistance have partly limited clinical application of BRD4 inhibitors 3 , 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation